KONSEP HILAL MAR’I (Analisis Terhadap Pandangan Anggota TIM Hisab Rukyat Kementerian Agama RI) - Bashori Alwi (JURNAL HAKAM, 2022)
One of the causes of differences in Eid al-Fitr so far is the difference among rukyat reckoning experts themselves regarding the concept of the new moon mar'i, where there are rukyat reckoning experts who say that the hilal is the lower disk, some even say it is the lower disk. on. This can clearly be a trigger for differences in starting the beginning of the Hijriyah month, especially Eid al-Fitr; that is, when the height of the new moon is critical (about 2 degrees), it may be that according to one rukyat reckoning expert and another, they have different views on the concept of the new moon mar'i; different, so the holidays are different. The researcher's initial hypothesis was that there was a difference in the concept of the new moon among members of the Hisab Rukyat Team of the Ministry of Religion of the Republic of Indonesia, because the ulama' differed in opinion regarding the entry of the early hijriyah month, especially the ulama' who allowed reckoning in determining the entry of the early hijriyah month, where there were those who used the criteria for the bright and light new moon. some wear the dark crescent. Besides that, the influence of a teacher's thoughts is quite large on the thoughts of his students, this also results in the similarity of views on the concept of the new moon of a student with his teacher, this happened to a member of the Hisab Rukyat Team of the Ministry of Religion of the Republic of Indonesia who combined the opinions of the majority of ulama' and the opinion of his teacher. (which follows the opinion of the minority ulama'). And after doing research, it turns out that the researcher's hypothesis is true.